Respuesta :

Answer:

The answer is y = 6x² + 42x + 60

Step-by-step explanation:

y = 6(x + 2)(x + 5)

y = 6 × (x + 2) × (x + 5)

y = 6 × (x² + 5x + 2x + 10)

y = 6 × (x² + 7x + 10)

y = 6x² + 42x + 60

Thus, The answer is y = 6x² + 42x + 60

-TheUnknownScientist

BohrJR

In the standard form, we will have: [tex]\sf {6x}^{2}+42x+60[/tex]

Development

We have the function:

[tex]\sf y = 6(x + 2)(x + 5)[/tex]

First, we must multiply the terms that are in parentheses. Applying distributive property.

[tex]\sf y = 6(x\cdot x+x\cdot5+2\cdot x+2\cdot5)[/tex]

We will perform the multiplication.

[tex]\sf y = 6({x}^{2}+5x+2x+10)[/tex]

We will perform the indicated operation.

[tex]\sf y = 6({x}^{2}+7x+10)[/tex]

Now, we can multiply the number 6 by what is in parentheses. Also applying distributive property.

[tex]\sf 6{x}^{2}+42+60[/tex]

Conclusion

The answer of this function is:

[tex]\boxed{\boxed{\sf 6{x}^{2}+42+60}}[/tex]